Comparison of efficacy and pharmacoeconomics of two helicobacter pylori eradication regimens in peptic ulcer disease - Syeda Zaineb Kubra Hussaini; Syeda Zaineb Humaira Hussaini; Ruheena Yasmeen; Bader Unnisa; Aamir Ali Asgar Syed; Md Nematullah Khan; Syed Ibrahim Hassan (Perspectives in Clinical Research, 2018)
Background: Helicobacter pylori, the cause of most peptic ulcer diseases, infects approximately 50% of the population worldwide. Indian data on cost and effectiveness of the standard first-line therapies for H. pylori eradication are scarce. Thus, the present study was aimed at comparing the cost and efficacy of two standard first-line therapies: Regimen I comprising pantoprazole (40 mg) plus amoxicillin (750 mg) plus clarithromycin (500 mg) (PAC) and Regimen II comprising rabeprazole (20 mg) plus amoxicillin (625 mg) plus metronidazole (200 mg) (RAM). Methodology: This prospective, observational, bottom-up study collected demographic, economic, diagnostic, and therapeutic data from 60 H. pylori-positive patients. The study was carried out for 6 months in the Gastroenterology Department of a Tertiary Care Hospital in Hyderabad, Telangana, India. Results: Health-care system perspective was used to account for direct costs. Average cost per patient for complete H. pylori eradication was Rs. 10,221 and Rs. 8568 for Regimen I and Regimen II, respectively. Inpatient cost was considerably higher than the outpatient cost. Diagnostic costs ranked first in direct costs, followed by hospitalization costs, medication costs, and finally, physician's office visit cost. Individual patient's costs difference between two regimens was found to be statistically significant. Overall, Regimen I proved to be more efficacious than Regimen II, but Regimen II proved to be more cost-effective than Regimen I. Furthermore, incremental cost-effectiveness analysis revealed additional cost of Rs. 127 per patient if the patient was treated with Regimen I instead of Regimen II. Conclusion: Our study showed that Regimen II (RAM) was more cost-effective than Regimen I (PAC), but PAC achieved faster H. pylori eradication than RAM. We assume that this study provides local clinical data as to which regimen may be useful in a particular patient. National Level Clinical Trials are required to further ascertain this conclusion.